Evaluation of monocyte chemotactic responsiveness in uraemic patients undergoing haemodialysis with different dialytic membranes - Ventura, M T; Di Corato, R; Giuliano, G; Matino, M G; Antonaci, S (Cytobios, 1998)
Recent data show that monocyte chemotactic peptide-1 (MCP-1), a chemotactic factor specific for monocytes, may play a central role in regulating the activation of these cells. For this reason, the production of MCP-1 in peripheral blood mononuclear cell (PBMC) cultures of eight healthy subjects, six chronic uraemic subjects under conservative treatment and six chronic uraemic patients undergoing haemodialysis (HD), was assessed. In the latter group of individuals, complement-activating membranes such as cuprophan (CU) were used for 1 month followed by biocompatible non-complement-activating membranes, like polymethylmetacrylate (PMMA) for the next 30 days. The chemotactic index (CI) elicited by PBMC supernatants from patients undergoing dialysis was found to be significantly higher than that obtained by supernatants recovered from normal subjects or uraemic patients on conservative therapy. Furthermore, the CI from PBMC supernatants having had contact with CU membranes was higher than that obtained from PBMC activated by PMMA. Finally, the increased chemotactic ability in the supernatants was closely correlated with the augmented MCP-1 gene expression and production, as assessed by in vitro hybridization studies.